1990
DOI: 10.1080/07399339009515913
|View full text |Cite
|
Sign up to set email alerts
|

Early patterns of maternal attachment

Abstract: The relationship between maternal-fetal attachment and maternal-child interaction was examined. The Maternal Fetal Attachment Scale (Cranley, 1981) was administered to 32 women between their 35th and 40th weeks of pregnancy. These mothers were observed again while they fed their infants once on the second and once on the third postpartum days. Their interactive behaviors were then rated on the Nursing Child Assessment Feeding Scale (University of Washington) and the Funke Mother-Infant Interaction Assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
1
25
0
3
Order By: Relevance
“…For other women, there may be a more consistent pattern in maternal relationship with her child from the antenatal period to postpartum. Several previous studies have indeed found evidence for a relationship between antenatal MFA and postnatal attachment; however, methods used and study findings have been inconsistent (Siddiqui and Hagglof 2000; Muller 1996; Bloom 1995; Fuller 1990), highlighting again the need for more definitive studies. Moreover, none of these studies examined pre- and postnatal attachment in the context of MDD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For other women, there may be a more consistent pattern in maternal relationship with her child from the antenatal period to postpartum. Several previous studies have indeed found evidence for a relationship between antenatal MFA and postnatal attachment; however, methods used and study findings have been inconsistent (Siddiqui and Hagglof 2000; Muller 1996; Bloom 1995; Fuller 1990), highlighting again the need for more definitive studies. Moreover, none of these studies examined pre- and postnatal attachment in the context of MDD.…”
Section: Discussionmentioning
confidence: 98%
“…Particular thoughts, feelings, and behaviors toward the fetus are common among pregnant women, though there is a wide degree of variability in the extent to which they are experienced (Leifer 1977; Cranley 1981). There is evidence for MFA to increase over the course of pregnancy (Grace 1989), and that attachment to the fetus in the antenatal period may lay the groundwork for the mother-to-infant relationship in the postpartum period (Siddiqui and Hagglof 2000; Muller 1993; Fuller 1990). It is well known that the early mother–infant relationship can influence future social, emotional, and cognitive development in the child (Ainsworth 1979; Ranson and Urichuk 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To collect data about these aspects is the main interest of the present study. Existing empirical evidences show that maternal attachment during pregnancy (for example, Fuller, 1990;Kemp et al, 1990) or immediately after delivery (for example, Cernadas et al, 2003) is associated with the quality of the mother-to-infant interaction and care (namely breastfeeding), which interfere in the child development (for example, Wiberg et al, 1989). Few are the studies that focus on the parent's emotional involvement with the newborn, and almost all are about mothers, so practically no information exists about fathers (Robson & Mandel, 1985).…”
Section: Parent-infant Initial Emotional Involvement 523mentioning
confidence: 99%
“…Previous studies have shown a significant association between maternal prenatal attachment and postnatal mother-baby interactions (e.g. J.R. Fuller, 1990;Siddiqui & Hägglöf, 2000) and family functioning (S. Fuller, Moore, & Lester, 1993). Investigating the emotional tie to the foetus and then to the baby is thus essential to understanding the transition to parenthood both for families who conceived spontaneously and those who conceived through IVF.…”
Section: Introductionmentioning
confidence: 98%